2012
DOI: 10.1007/s00535-012-0687-8
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric administration of rikkunshito stimulates upper gastrointestinal motility and gastric emptying in conscious dogs

Abstract: Intragastric administration of rikkunshito stimulates gastrointestinal contractions in the interdigestive state through cholinergic neurons and 5-HT type 3 receptors. Moreover, rikkunshito increases plasma acylated ghrelin levels. Rikkunshito may alleviate gastrointestinal disorders through its prokinetic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…Additionally, increasing evidence from experimental animal models has shown that rikkunshito ameliorates several types of anorexia (23,24,57). It has been reported that with rikkushito there is an increase in the secretion of the orexigenic hormone ghrelin by the inhibition of 5-HT2B/2C receptors, an enhancement of ghrelin receptor (GHSR) signaling efficiency, and a facilitation of gastric emptying and gastric adaptive relaxation, all of which may contribute to ameliorate anorexia (24,32,57,60,64). Herein, we examined specifically the efficacy of rikkunshito in ameliorating anorexia symptoms in our novel cancer cachexia rat models.…”
mentioning
confidence: 99%
“…Additionally, increasing evidence from experimental animal models has shown that rikkunshito ameliorates several types of anorexia (23,24,57). It has been reported that with rikkushito there is an increase in the secretion of the orexigenic hormone ghrelin by the inhibition of 5-HT2B/2C receptors, an enhancement of ghrelin receptor (GHSR) signaling efficiency, and a facilitation of gastric emptying and gastric adaptive relaxation, all of which may contribute to ameliorate anorexia (24,32,57,60,64). Herein, we examined specifically the efficacy of rikkunshito in ameliorating anorexia symptoms in our novel cancer cachexia rat models.…”
mentioning
confidence: 99%
“…Ghrelin is expressed by GHRL gene, several SNP are informed for it. In literature is actively studied the SNP allele polymorphism with obesity [10,11], food behavior disorders [12] and metabolism disturbances [13], and also with gastric acid secretion [14] and fast stomach emptying [15,16]. Mutations in this gene can cause low levels of ghrelin, registered at obesity [17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we were able to compare the effects of various reagents in the same animals. In this context, four to six dogs have been used in recent studies from our institution (Hayashi et al 2010;Sato et al 2010a) and other institutions (Dong et al 2005;Morita et al 2012;Yanai et al 2013).…”
Section: Discussionmentioning
confidence: 99%